CSR performance and the cost of financial debt in emerging MENA economies - Jeriji, Dr. Maher (The journal of contemporary issues in business and government, 2022)
This study tackles the debate regarding the effect of corporate social responsibility (CSR) performance on cost of debt. The relationship between corporate CSR performance and the interest rate of debt is examined using the system GMM technique estimator on 243 listed non- financial firms from 10 MENA emerging countries (Bahrain, Egypt, Jordan, Kuwait, Morocco, Oman, Qatar, Saudi Arabia, Turkey, and the United Arab Emirates) during the period 2011-2020. We provide substantial evidence that the association between CSR performance and the interest rate on debt - the accounting measure of the cost of debt, is significant and negative. This support stakeholders’ value maximization view and suggest that lenders reward better CSR performance. However, findings show that firms with more transparent CSR reporting are penalized by institutional creditors. Our findings provide more in-depth evidence on why companies should improve their CSR performance while paying more attention to CSR reporting practices.